Circulating Cell-Free DNA and Colorectal Cancer: A Systematic Review - Vymetalkova, Veronika; Cervena, Klara; Bartu, Linda; Vodicka, Pavel (International journal of molecular sciences, 2018)
There is a strong demand for the identification of new biomarkers in colorectal cancer (CRC) diagnosis. Among all liquid biopsy analysts, cell-free circulating DNA (cfDNA) is probably the most promising tool with respect to the identification of minimal residual diseases, assessment of treatment response and prognosis, and identification of resistance mechanisms. Circulating cell-free tumor DNA (ctDNA) maintains the same genomic signatures that are present in the matching tumor tissue allowing for the quantitative and qualitative evaluation of mutation burdens in body fluids. Thus, ctDNA-based research represents a non-invasive method for cancer detection. Among the numerous possible applications, the diagnostic, predictive, and/or prognostic utility of ctDNA in CRC has attracted intense research during the last few years. In the present review, we will describe the different aspects related to cfDNA research and evidence from studies supporting its potential use in CRC diagnoses and the improvement of therapy efficacy. We believe that ctDNA-based research should be considered as key towards the introduction of personalized medicine and patient benefits.
Keywords: rektum; Circulating Tumor DNA; colorectal cancer; kolorektální nádory; Prognosis; Colorectal Neoplasms; Liquid Biopsy; tekutá biopsie; Biomarkers, Tumor; Colon; liquid biopsy; prognóza; nádorové biomarkery; zvířata; Humans; cirkulující nádorová DNA; kolon; cell-free DNA; Rectum; lidé; Animals